THE RELEVANCE OF EXCESS CASH TO EXPLAIN FINANCIAL PERFORMANCE AND STOCK RETURNS IN BRAZILIAN LISTED FIRMS - Miranda, Romario Borges; Pimentel, Renê Coppe; Bezerra, Francisco Antonio (Advances in Scientific and Applied Accounting, 2019)
This paper analyzes the determinants and consequences of excess cash (ECM) in relationship to financial performance and stock returns in the Brazilian market which is characterized by concentration in the stock market given that Brazil is an emerging country with high political, economic and institutional uncertainties. This analysis is based on 290 Brazilian non-financial companies listed in the B3 stock exchange from 2000 to 2017. The results suggest that firms with higher excess of cash are those with higher financial performance and higher stock returns which indicates that those firms have higher potential for future growth, therefore firms hold cash for speculative reasons. In pairwise analysis, ECM and firm systemic risk had a negative and significant association, suggesting that excess of cash can also be a potential instrument for risk reduction however overall the results of risk variable do not indicate a consistent role. Analysis of lag structure of ECM indicates a positive association between current ECM and short-term (one-year) returns with stock prices, suggesting that market agents use excess cash to take advantage of investment opportunities. Therefore all evidence suggests that firms retain cash based on the speculative motive.